2014
DOI: 10.1111/jog.12471
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and incidence of post‐partum depression: A longitudinal cohort study

Abstract: A high rate of new cases of PPD was identified in Iranian women. A combination of psychological, sociological, obstetric and sociodemographic factors can render mothers vulnerable to post-partum depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
44
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 54 publications
8
44
1
Order By: Relevance
“…We found that GDM substantially increased a woman’s risk of postpartum depression approximately fourfold. Our findings in a low-risk, diverse, US sample confirm those of a prior study from Iran [15]. Interestingly, other studies of the association between GDM and postpartum depression have been null, but these studies either assessed depression much later, at 6 months postpartum [12], or used a self-report of depression [13], unlike our study, which used a validated measure of depressive symptoms at 6 weeks postpartum.…”
Section: Discussionsupporting
confidence: 81%
“…We found that GDM substantially increased a woman’s risk of postpartum depression approximately fourfold. Our findings in a low-risk, diverse, US sample confirm those of a prior study from Iran [15]. Interestingly, other studies of the association between GDM and postpartum depression have been null, but these studies either assessed depression much later, at 6 months postpartum [12], or used a self-report of depression [13], unlike our study, which used a validated measure of depressive symptoms at 6 weeks postpartum.…”
Section: Discussionsupporting
confidence: 81%
“…Of these, 46 publications were selected for inclusion[20-65]. Manual screening of bibliographies identified two additional relevant studies[66,67].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 48 publications were included in this review (Figure 1, Table 1, Table 2, Table 3, Supplementary Table 1). Of these, 30 described prospective observational studies[20,21,23,24,26,27,29-31,34,35,37,38,41,43-45,47-49,51,54,57,58,60-62,65-67], 15 described retrospective observational studies[22,25,28,32,39,40,42,46,50,53,55,56,59,63,64], and three described randomized controlled trials (RCTs)[33,36,52], two of which reported only baseline data[36,52]. Two publications described the same study, but reported different subgroup analyses[23,29].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations